2017
DOI: 10.1159/000477309
|View full text |Cite
|
Sign up to set email alerts
|

Emery-Dreifuss Muscular Dystrophy-Associated Mutant Forms of Lamin A Recruit the Stress Responsive Protein Ankrd2 into the Nucleus, Affecting the Cellular Response to Oxidative Stress

Abstract: Background: Ankrd2 is a stress responsive protein mainly expressed in muscle cells. Upon the application of oxidative stress, Ankrd2 translocates into the nucleus where it regulates the activity of genes involved in cellular response to stress. Emery-Dreifuss Muscular Dystrophy 2 (EDMD2) is a muscular disorder caused by mutations of the gene encoding lamin A, LMNA. As well as many phenotypic abnormalities, EDMD2 muscle cells also feature a permanent basal stress state, the underlying molecular mechanisms of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…In fact, double immunolabeling of Samp1 and laminin alpha 2, which lines the basal lamina of myofibers, demonstrated that nuclei inside control muscle fibers were Samp1 positive and the protein was located at the nuclear periphery, which was previously reported in Reference [ 30 ], while interstitial nuclei presented a faint staining ( Figure 4 d). In EDMD2 myonuclei bearing the H506P LMNA mutation [ 32 ], Samp1 was mis-localized in the vast majority (80%) of examined myofibers ( Figure 4 d) possibly due to a loss of interaction with farnesylated prelamin A, which is dramatically reduced in EDMD2 muscle fibers [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, double immunolabeling of Samp1 and laminin alpha 2, which lines the basal lamina of myofibers, demonstrated that nuclei inside control muscle fibers were Samp1 positive and the protein was located at the nuclear periphery, which was previously reported in Reference [ 30 ], while interstitial nuclei presented a faint staining ( Figure 4 d). In EDMD2 myonuclei bearing the H506P LMNA mutation [ 32 ], Samp1 was mis-localized in the vast majority (80%) of examined myofibers ( Figure 4 d) possibly due to a loss of interaction with farnesylated prelamin A, which is dramatically reduced in EDMD2 muscle fibers [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the EDMD2 myoblasts used in this study, the R190Q/R249Q LMNA mutations had been determined in a single allele [ 31 ]. Moreover, we used myoblasts from an EDMD2 patient harboring the H506P LMNA mutation [ 32 ] and a muscular dystrophy linked to the compound heterozygous P68D/G338S SUN1 mutation [ 17 ]. Accumulation of non-farnesylated prelamin A was obtained after 18 h of treatment of differentiating myoblasts with 20 µM Mevinolin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Human myoblast and fibroblast cultures were obtained from healthy donors, LGMD1B patients carrying the Y259D LMNA mutation [ 6 ] or EDMD2 patients bearing the H506P LMNA mutation [ 35 ]. Tenocytes were established from biopsies of healthy donors undergoing orthopaedic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…However, prelamin A has also been shown to regulate early events of myoblast differentiation, as caveolin 3 expression [ 16 ] and nuclear positioning in human muscle cells [ 17 ]. We also demonstrated that lamin A and prelamin A are complexed to Ankrd2, a protein involved in the transcriptional response to stress during myoblast differentiation [ 18 , 19 ]. LMNA gene mutations are responsible for the onset of autosomal dominant Emery–Dreifuss muscular dystrophy (EDMD2), which is characterized by skeletal muscle weakness and wasting, joint contractures and cardiomyopathy [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%